Diagnostic kit for rice blight resistance - Eom, Joon-Seob; Luo, Dangping; Atienza-Grande, Genelou; Yang, Jungil; Ji, Chonghui; Thi Luu, Van; Huguet-Tapia, José C.; Char, Si Nian; Liu, Bo; Nguyen, Hanna; Schmidt, Sarah Maria; Szurek, Boris; et al. (Springer, 2019)
Blight-resistant rice lines are the most effective solution for bacterial blight, caused byXanthomonas oryzaepv.oryzae(Xoo). Key resistance mechanisms involveSWEETgenes as susceptibility factors. Bacterial transcription activator-like (TAL) effectors bind to effector-binding elements (EBEs) inSWEETgene promoters and induceSWEETgenes. EBE variants that cannot be recognized by TAL effectors abrogate induction, causing resistance. Here we describe a diagnostic kit to enable analysis of bacterial blight in the field and identification of suitable resistant lines. Specifically, we include aSWEETpromoter database, RT–PCR primers for detectingSWEETinduction, engineered reporter rice lines to visualize SWEET protein accumulation and knock-out rice lines to identify virulence mechanisms in bacterial isolates. We also developed CRISPR–Cas9 genome-edited Kitaake rice to evaluate the efficacy of EBE mutations in resistance, software to predict the optimal resistance gene set for a specific geographic region, and two resistant ‘mega’ rice lines that will empower farmers to plant lines that are most likely to resist rice blight.